2014
DOI: 10.2478/johr-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Leaves Of Cut Rose Flower Convert Exogenously Applied Glucose To Sucrose And Translocate It To Petals

Abstract: To understand the role that the leaves play in the translocation of soluble carbohydrates in cut rose flowers, we first evaluated the effect of leaf removal on flower quality and the sugar content in petals. Cut rose flowers with leaves had higher soluble sugar content in petals compared with cut flower without leaves. Next, we treated cut flowers with radioactive glucose to clarify translocation routes of exogenously applied sugar. There was no significant difference between the specific radioactivity of sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…In Calendula arvensis, its flower opening and closing circadian rhythm followed the light-dark cycle in a manner dependent upon which flower had been exposed when the leaves were subjected to a different light-dark cycle from the flowers (van Doorn & van Meeteren 2003). In cut roses, rose petals can perceive red and blue light and synchronize their growth to photoperiods (Horibe & Yamada 2014a;Horibe & Yamada 2014b;Horibe et al 2014), but it is still unclear which photoreceptors play a role in receiving red and blue light and what reactions are involved between perception of light and rhythmic flower opening. Another report showed that a relatively slow phytochrome reaction is involved in the perception of the duration of light or darkness (Lumsden 1991).…”
Section: Diurnal Rhythmic Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…In Calendula arvensis, its flower opening and closing circadian rhythm followed the light-dark cycle in a manner dependent upon which flower had been exposed when the leaves were subjected to a different light-dark cycle from the flowers (van Doorn & van Meeteren 2003). In cut roses, rose petals can perceive red and blue light and synchronize their growth to photoperiods (Horibe & Yamada 2014a;Horibe & Yamada 2014b;Horibe et al 2014), but it is still unclear which photoreceptors play a role in receiving red and blue light and what reactions are involved between perception of light and rhythmic flower opening. Another report showed that a relatively slow phytochrome reaction is involved in the perception of the duration of light or darkness (Lumsden 1991).…”
Section: Diurnal Rhythmic Growthmentioning
confidence: 99%
“…In the Asiatic hybrid lily, flower opening has been shown to proceed irregularly if it was kept in continuous darkness, indicating the importance of changing from light to darkness for appropriate timing of flower opening (Bieleski et al 2000). In the hybrid tea rose, Horibe et al (2014) reported that flower opening showed a diurnal rhythm under a 12-h photoperiod and constant dark conditions, although rhythmic flower opening under constant dark was not as clear as that of cut flowers kept under 12-h light and 12-h dark cycles. However, cut roses maintained under constant light did not show rhythmic growth and kept opening slowly until fully opened.…”
Section: Diurnal Rhythmic Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, orchids (Cymbidium hybrid 'Red Princess') treated with 5% sucrose pulsing had a longer vase life of 56 days (De et al, 2014). In addition, Horibe et al (2014) also showed the importance of leaves in the translocation of sugar. Flowers cut from roses with leaves had a higher soluble sugar content in the petals compared with cut flowers without leaves.…”
Section: Carbohydratesmentioning
confidence: 97%